2007
DOI: 10.1093/deafed/enm022
|View full text |Cite
|
Sign up to set email alerts
|

Visual Spatial Representation in Mathematical Problem Solving by Deaf and Hearing Students

Abstract: This research examined the use of visual-spatial representation by deaf and hearing students while solving mathematical problems. The connection between spatial skills and success in mathematics performance has long been established in the literature. This study examined the distinction between visual-spatial "schematic" representations that encode the spatial relations described in a problem versus visual-spatial "pictorial" representations that encode only the visual appearance of the objects described in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 28 publications
10
39
0
1
Order By: Relevance
“…Inline with these earlier findings, the current study showed that spatial ability is a significant and relevant basic ability which increases the chance of solving a word problem successfully (Blatto-Vallee et al, 2007;Boonen et al, 2013;Hegarty & Kozhevnikov, 1999). In particular, our findings clarified the importance of spatial ability for the accurate visual-schematic representation type.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Inline with these earlier findings, the current study showed that spatial ability is a significant and relevant basic ability which increases the chance of solving a word problem successfully (Blatto-Vallee et al, 2007;Boonen et al, 2013;Hegarty & Kozhevnikov, 1999). In particular, our findings clarified the importance of spatial ability for the accurate visual-schematic representation type.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, a positive relationship between visual representation type and word problem solving performance has been established by calculating correlations between the total amount of (specific) visual representations produced and the total amount of correctly solved word problems (e.g., Blatto-Vallee, Kelly, Gaustad, Porter, & Fonzi, 2007;Guoliang, 2003;Hegarty & Kozhevnikov, 1999;Krawec, 2010Krawec, , 2012Van Garderen, 2006;Van Garderen & Montague, 2003). However, calculating the correlation between two sum scores is an example of a test-level approach entailing limitations to be considered in this study.…”
mentioning
confidence: 99%
“…Besides the positive relation between constructive play and children’s spatial ability, a positive relation between spatial ability and mathematical ability, particularly mathematical word problem solving, is also reported in several studies (Guay and McDaniel, 1977; Lean and Clements, 1981; Tracy, 1987; Casey et al, 1992; Hegarty and Kozhevnikov, 1999; Kozhevnikov et al, 2002; Blatto-Vallee et al, 2007; Beentjes, 2008). Blatto-Vallee et al (2007) showed, for example, that spatial ability explained almost 20% of unique variance in mathematical word problem-solving performance.…”
Section: Introductionmentioning
confidence: 64%
“…The aim of the present study is to examine the link between children’s constructive play activities and two interrelated factors, namely spatial ability and mathematical word problem-solving performance. Although a positive relation between constructive play and spatial ability is reported by several authors (e.g., Bjorklund and Douglas-Brown, 2008; Levine et al, 2012) as well as a positive relation between spatial ability and mathematical word problem-solving performance (Blatto-Vallee et al, 2007; Beentjes, 2008; Casey et al, 2008), a relation between constructive play and mathematical word problem-solving performance is barely investigated. A possible reason for this absence is that spatial ability acts as a mediator in the relation between children’s constructive play activities and their performances on mathematical word problems.…”
Section: Introductionmentioning
confidence: 97%
“…Esta hipótese tem sido reiterada por vários estudos na área que demonstraram que as crianças surdas apresentam um tempo e trajetória de desenvolvimento similar, ou até mesmo superior, ao das crianças ouvintes em: reco nhecimento facial, construções com blocos lógicos, percepção de movimentos, memória espacial e localização espacial (BEVALIER et al, 2006;BLATTO-VALLEE et al, 2007;SATO et al, 2007). A superioridade no desenvolvimento destas funções cognitivas deve-se ao uso da língua de Disponível em <http://www.cedes.unicamp.br> Habilidades matemáticas iniciais em crianças surdas e ouvintes sinais que, por suas características visuo-espaciais, contribui positivamente para o desenvolvimento das habilidades de manipulação da informação visual e espacial (BULL et al, 2006;BLATTO-VALLEE et al, 2007). Crianças surdas que não são expostas a estímulos linguísticos e não recebem educação apropriada, em idade apropriada, não demonstram esta similaridade e superioridade no desenvolvimento destas funções cognitivas.…”
unclassified